Causes of Discordance between Allometries at and above Species Level: An Example with Aquatic Beetles - Higginson, Dawn M; Badyaev, Alexander V; Segraves, Kari A; Pitnick, Scott (The American naturalist, 2015)
Covariation among organismal traits is nearly universal, occurring both within and among species (static and evolutionary allometry, respectively). If conserved developmental processes produce similarity in static and evolutionary allometry, then when species differ in development, it should be expressed in discordance between allometries. Here, we investigate whether rapidly evolving developmental processes result in discordant static and evolutionary allometries attributable to trade-offs in resource acquisition, allocation, or growth across 30 species of aquatic beetles. The highly divergent sperm phenotypes of these beetles might be an important contributor to allometric evolution of testis and accessory gland mass through altered requirements for the production of sperm and seminal fluids. We documented extensive discordance between static and evolutionary allometries, indicating that allometric relationships are flexibly modified over short time periods but subject to constraint over longer time spans. Among species, sperm phenotype did not influence relative investment in accessory glands but was weakly associated with investment in testes. Furthermore, except when sperm were long and simple, sperm phenotype was not associated with species-specific modification of the allometry of testis/accessory gland mass and body size. Our results demonstrate the utility of allometric discordance to infer species differences in the provisioning and growth of concurrently developing traits.